An Assessment of how Polokwane local municipality executes their mandate in water supply to Matlou and Letsokoane Residents - Molote, Phuti Ignatius; Moeti, Kabelo Boikhutso (Penerbit Universiti Kebangsaan Malaysia, 2024)
The main aim of this study is to assess water supply in general and specifically to “assess on how the Polokwane municipality executes their mandate in terms of water supply to Matlou and Letsokoane Residents. This was done on a case study about Matlou and Letsokoane inhabitants were chosen as a setting for the study. A mixed method approach was used for the study combining structured questionnaires and open-ended interviews. The findings of the study have showed that there is poor water supply to two affected rural communities by the Polokwane local municipality. Amongst contributing factors the increase in population growth in that area is a major problem as well as residents tampering with infrastructure, theft and no interventions by political representatives when there is no water. This has resulted in inadequate provision of clean water resources. Water supply Value chain model has been proposed emanating from the findings of the research study to be implemented by the Polokwane local municipality to curb the problem of water supply to the rural communities. Lessons that can be learned from this study include the following: consultation with the communities through ward councilors which include educational aspect such as preservation of water as a source of human life, providing a compelling case for concertizing the community with an attempt to reduce illegal activities as cited in the study regarding the steeling of water taps.